Integrasi Turoth dan Media Digital dalam Pendidikan Islam Moderat: Analisis Konten Kajian Gus Kautsar terhadap Generasi Z - Shofil Albab; Muhammad Rofiq (CV. ALIM'SPUBLISHING, 2026)
This study analyzes the integration of turoth (classical Islamic scholarship) and digital media in moderate Islamic education through Gus Kautsar’s YouTube lectures. Amid concerns that religious digitalization may simplify Islamic teachings and reduce epistemological depth, this research examines whether turoth transmission in digital platforms maintains traditional scholarly structures. Using a qualitative approach with thematic content analysis, this study analyzes three classical text-based lecture videos published between January and March 2024. The findings show that turoth is represented through direct reading of Arabic classical texts, hierarchical argument structures (Qur’an–Hadith–Ulama), references to madhhab authorities, and contextualization of contemporary digital issues. The adaptation identified is pedagogical rather than epistemological, reflected in episodic segmentation, communicative translation, and contextual illustrations suited to Generation Z’s learning patterns. Furthermore, moderate Islamic education in the analyzed content emerges not through normative slogans, but through systematic engagement with classical texts. This study demonstrates that digital media can function as a medium for recontextualizing Islamic tradition while fostering moderate religious values among Generation Z in the digital era.